Computational Statistics (Journal) - Wolfgang Karl Härdle; Yuichi Mori; Jürgen Symanzik (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
Computational Statistics is an international journal that fosters the publication of applications and methodological research in the field of computational statistics. In this article, we will discuss the motivation, history, some specialties, and the future scope of this journal.
Keywords: C63; C88; Y30; 330; international journal; history of the journal; specialties of the journal; online communications; Statistische Methodenlehre; PC-Software; Computergestütztes Verfahren; Fachzeitschrift; Welt